Variação espacial e temporal da precipitação no estado do Pará - MORAES, Bergson Cavalcanti de (Instituto Nacional de Pesquisas da Amazônia, 2013)
Studies about the climatology of precipitation in the State of Pará are essential for the planning of agricultural activities. The variation of annual and seasonal precipitation in Pará was analysed based on a historic series of 23 years (1976 1998) of daily rainfall data. The analysis was made for 31 locations in Pará, using geographic information systems techniques, with the results presented in maps. The variability of annual and seasonal precipitation was characterized based on the coefficient of variation and the index of relative interanual variability. The variation of these coefficients for the annual precipitation in Pará was 15 to 30 %. The monthly characteristics of the wet season, in terms of beginning, end and duration, were determined using a criteria proposed by KASSAM (1979). The variation between early planting dates and late planting dates were identified by the periods of julian days of 309 319 and 353 363, respectively.